2013
DOI: 10.1155/2013/828373
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Cementoblastoma: A Rare Case Report

Abstract: Benign cementoblastoma is a rare ectomesenchymal odontogenic tumor that originates from the root of the tooth and that is characterized by the formation of cementum-like tissue. A 60-year old man was referred to us complaining of pain in his right jaw. The patient underwent TC dental scan of the mandible, which highlighted the presence of three well-circumscribed, round, unilocular neoformations of radiopaque appearance with a radiotransparent edge, one of which was in close contact with the roots of the lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 6 publications
0
14
0
4
Order By: Relevance
“…Sementoblastoma diş kökünden orijin alır ve radyografide diş kökleri ile yakın ilişkili ince radyolüsens hat ile çevrili radyoopak yığınlar olarak görülür. 4,[14][15][16][17][18] Odontoma mezenşimal ve epitelyal dental elementler içeren en yaygın bening odontojenik tümörlerdir. Kompaund odontoma yaygın olarak anterior maksillayı etkileyen ve radyografide diş benzeri uniloküler radyoopak alanlar içeren lezyonlardır.…”
Section: Discussionunclassified
“…Sementoblastoma diş kökünden orijin alır ve radyografide diş kökleri ile yakın ilişkili ince radyolüsens hat ile çevrili radyoopak yığınlar olarak görülür. 4,[14][15][16][17][18] Odontoma mezenşimal ve epitelyal dental elementler içeren en yaygın bening odontojenik tümörlerdir. Kompaund odontoma yaygın olarak anterior maksillayı etkileyen ve radyografide diş benzeri uniloküler radyoopak alanlar içeren lezyonlardır.…”
Section: Discussionunclassified
“…This treatment has been applied in other studies with good clinical results and absence[ 13 , 14 ] of recurrence or rate of recurrence similar to that of treatment by tooth extraction[ 1 ]. However, removal of the affected tooth is still the option most indicated in case reports and previous studies[ 2 , 7 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the high rates of recurrence (approximately 31.7%) associated with incomplete removal of the lesion[ 1 ], the treatment of cementoblastoma most indicated in the literature, is removal of the tooth together with the tumor[ 6 , 7 ]. However, endodontic treatment of the affected tooth associated with apicoectomy during removal of the lesion is cited as an alternative[ 1 ], allowing the tooth to be maintained in function[ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…(3) Cementoblastoma is rare in the oral cavity and accounts for less than 1% of all odontogenic tumors and is currently classified by the 2005 WHO as an ectomesenchymal odontogenic tumor with or without odontogenic epithelium that originates from dental roots and is characterized by cementum formation. (3,4,7,8) Cementoblastoma or true Cementoma is a slow growing tumor mostly involving the permanent dentition. It is especially uncommon in children.…”
Section: Discussionmentioning
confidence: 99%
“…(3,4,5,8) The tumor has been also associated with multiple teeth or impacted molars. (5,7) No significant sex predilection has been reported, however some authors have reported contradictory findings. (4) The average tumor size is 2.1 cm.…”
Section: Discussionmentioning
confidence: 99%